2004
DOI: 10.4049/jimmunol.172.9.5356
|View full text |Cite
|
Sign up to set email alerts
|

Deficiencies in Gut NK Cell Number and Function Precede Diabetes Onset in BB Rats

Abstract: Defects in the intestinal immune system may contribute to the pathogenesis of autoimmune diseases. Intraepithelial lymphocytes represent a substantial fraction of gut-associated lymphocytes, but their function in mucosal immunity is unclear. A newly described population of NK cells that spontaneously secrete IL-4 and IFN-γ is present in the intraepithelial lymphocyte compartment of the rat. We hypothesized that defects in the number or function of these cells would be present in rats susceptible to autoimmunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 42 publications
0
26
1
Order By: Relevance
“…Previous studies have suggested that Treg cells do not interact directly with Teff cells; instead, they may suppress target Teff cells through the interaction with antigen-presenting cells (40,41). Our results do not exclude the possible involvement of, for example, dendritic natural killer T-cells and natural killer cells, which have been suggested to play a role during islet inflammation and diabetes onset (27,(42)(43)(44)(45)(46). Further studies are needed to determine the relative contribution of these different possibilities.…”
Section: Discussioncontrasting
confidence: 67%
“…Previous studies have suggested that Treg cells do not interact directly with Teff cells; instead, they may suppress target Teff cells through the interaction with antigen-presenting cells (40,41). Our results do not exclude the possible involvement of, for example, dendritic natural killer T-cells and natural killer cells, which have been suggested to play a role during islet inflammation and diabetes onset (27,(42)(43)(44)(45)(46). Further studies are needed to determine the relative contribution of these different possibilities.…”
Section: Discussioncontrasting
confidence: 67%
“…[30][31][32] Gimap5 deficiency interfered with virtually all stages of mouse NK development and was incompatible with NK formation in any of the anatomic compartments thought to provide a permissive environment for NK maturation, including BM, spleen, lymph nodes, and liver. The presence of a small number of V␣ TCR-positive invariant NKT (iNKT) cells (as defined by ␣-GalCer/CD1d staining) indicates that some of these cells can develop and successfully rearrange their TCR chains.…”
Section: Discussionmentioning
confidence: 99%
“…These cells lie in close proximity to the intestinal epithelial barrier and facilitate immune responsiveness, especially in the presence of elevated intestinal epithelial permeability (6). Recent reports suggest that quantitative and͞or qualitative deficiencies in a subset of NK cells occur in several autoimmune diseases, including type 1 diabetes (T1D) (7) and celiac disease (CD) (8). These cells play a pivotal role in the maintenance of immune tolerance by down-regulating the immune response to foreign antigens when they gain access beyond the intestinal mucosal barrier (6).…”
mentioning
confidence: 99%